Group insurance and welfare scheme for public servants in Banlgadesh: an appraisal of economic efficiency and effectiveness - Alam, Md. Nurul (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2006.